Pengaruh Media Video Bandicam Terhadap Bahasa Anak Di Taman Kanak-kanak Negeri Pembina Kabupaten Tanah Datar - Anggraini, Dini Saumi; Jaya, Indra (Didaktika, 2021)
To develop and improve children's language, media is needed. The media plays an important role in learning activities because it clarifies the delivery of messages and reduces verbality, deepens understanding of the material, and demonstrates concrete abstract understanding. This study aims to determine the effect of Bandicam video media on children's language in TK Negeri Pembina Kabupaten Tanah Datar. This study uses quantitative research using an experimental approach. This research uses an assessment indicator instrument. The results of this study indicate that there is a significant effect and difference from the use of Bandicam video media on children's language as shown by (1) the post-test results of the experimental class and control class after being given different treatments there are significant differences, namely the experimental class 26.76 and control class is 14.26. (2) The use of this Bandicam video media influences children's language. The real evidence can be seen from the post-test results. In the results of hypothesis testing obtained the value of sig. (2-tailed) is 0.000 with a significant value of 0.05 where 0.000 is smaller than 0.05 so that Ho is rejected and Ha is accepted. So the use of Bandicam video media on children's language in the TK Negeri Pembina Kabupaten Tanah Datar has a significant influence. And the use of Bandicam video media has benefits in that it can give meaning to cooperation between teachers and children to develop children's language.